Discovery of common and rare genetic risk variants for colorectal cancer. (January 2019) - Huyghe, Jeroen; Bien, Stephanie; Harrison, Tabitha; Kang, Hyun; Chen, Sai; Schmit, Stephanie; Conti, David; Qu, Conghui; Jeon, Jihyoun; Edlund, Christopher; Greenside, Peyton; Wainberg, Michael; et al.
Abstract To further dissect the genetic architecture of colorectal cancer (CRC), we performed whole-genome sequencing of 1, 439 cases and 720 controls, imputed discovered sequence variants and Haplotype Reference Consortium panel variants into genome-wide association study data, and tested for association in 34, 869 cases and 29, 051 controls. Findings were followed up in an additional 23, 262 cases and 38, 296 controls. We discovered a strongly protective 0.3% frequency variant signal atCHD1 . In a combined meta-analysis of 125, 478 individuals, we identified 40 new independent signals atP < 5 × 10−8, bringing the number of known independent signals for CRC to 100. New signals implicate lower-frequency variants, Krüppel-like factors, Hedgehog signaling, Hippo-YAP signaling, long noncoding RNAs and somatic drivers, and support a role for immune function. Heritability analyses suggest that CRC risk is highly polygenic, and larger, more comprehensive studies enabling rare variant analysis will improve understanding of biology underlying this risk and influence personalized screening strategies and drug development. Genome-wide association analyses based on whole-genome sequencing and imputation identify 40 new risk variants for colorectal cancer, including a strongly protective low-frequency variant atCHD1 and loci implicating signaling and immune function in disease etiology.